META ANALISIS MODEL PBL TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA DI SD (PIONIR: JURNAL PENDIDIKAN, 2020)
The purpose of research is by to assess related to influence model Problem Based Learning (PBL) in improve critical thinking skill. Model Problem Based Learning (PBL) is one of learning model who presents the problem to solve or resolved. Research methodology used the meta research analysis. Data collection technique used is non test by means tracing articles is in online with journal used google cendekia and google schoolar. Of the results of the investigation 17 articles obtained through google cendekia. Model based on the results indicate Problem Based Learning (PBL) to increase the capacity to think critical students from 7 % to lowest highest % 29, 96 with an average % 18, 11.
Keywords: Meta Analyze; Problem Based Learning; Critical Thinking Skill